(untitled) (International Journal of Food and Nutritional Sciences, 2022)
High-performance computing (HPC) is at the forefront of modern computational advancements, enabling breakthroughs in science, engineering, and industry. This paper provides a comprehensive overview of HPC, emphasizing its historical evolution, various architectures, and parallel computing paradigms. It explores the crucial role of HPC in realworld applications, from weather forecasting to scientific simulations, while also addressing the challenges and limitations of this technology, including energy efficiency and data management.